Spontaneous free floating carotid artery thrombosis. (7th June 2013) - Graham, Ruth; Blaszczynski, Marek
Abstract : A 64-year-old man, with no history of trauma, presented with transient visual loss. He was diagnosed with amaurosis fugax and started on dipyridamole and simvastatin. An inconclusive ultrasound (US) Doppler was followed by CT angiogram (CTA) and MRI, which demonstrated free floating intraluminal thrombus in the distal right common carotid artery. ECG showed sinus rhythm and an echocardiogram showed no cardiac thrombus. Following discussion at the vascular multidisciplinary team the decision was made to treat with intravenous heparin followed by warfarin. He has been regularly followed up with CTA/USS, the most recent (Oct 2012) showing no evidence of thrombus. He has had no further symptoms. Despite no initial aetiology being found we suggest that his undiagnosed oesophageal carcinoma (diagnosed 5 months after initial presentation) could have been responsible for a hypercoagulability state giving an increased risk of thrombosis and leading to the thrombus in the common carotid artery.